Influence of ATXN2 intermediate CAG repeats, 9bp duplication and alternative splicing on SCA3 pathogenesis - Lauerer, Marilena; Faber, Jennifer; Casadei, Nicolas; Santana, Magda M.; Auburger, Georg; Pogoda, Michaela; Admard, Jakob; Kaupp, Lea; Kos, Patricia Laura; Raposo, Mafalda; Lima, Manuela; de Almeida, Luis Pereira; et al. (Acta Neuropathologica Communications, 2025)
Spinocerebellar ataxia type 3 (SCA3) is a neurodegenerative disease whose exact disease pathogenesis is not yet fully understood. We performed a genetic in-depth analysis of ataxin-2 (ATXN2), a gene that has already been described as a modulator of neurodegenerative diseases. We focused on the influence of an intermediate CAG repeat, a 9bp duplication (9bp), and isoform expression of ATXN2 on the pathogenesis of SCA3.